Comparative analysis of motoric abilities between two groups of football referees from Kosovo - Bylbyl Sokoli; Florian Miftari; Agron Thaqi (Kazimierz Wielki University, 2018)
The aim of this research is to define the difference between two groups of football referees from Kosovo; 15 referees from Super league and 15 referees from First league, based on some motoric abilities. Referees have been tested on these motor abilities; 6x40m running, 7x150m running and 7x50m walking. Equipment and standard procedures are used during the test. In each of these motor abilities are counted central, basic and distribution parameters; arithmetical average, standard deviation, minimal rate, maximal rate, and distribution parameters (Skewness, Kortosis). In order to prove the difference between those two groups of referees is applied T-test analysis. The level of significance was set (p